Candidate Biomarkers for Fatigue in Systemic Lupus Erythematosus: A Critical Review - A. Mahieu, Mary; Ramsey-Goldman, Rosalind (Current Rheumatology Reviews, 2017)
Fatigue impacts 80-90% of patients with systemic lupus erythematosus (SLE), and an incomplete understanding of fatigue mechanisms limits effective treatment. Disease activity indices and laboratory markers inconsistently correlate with fatigue severity in SLE populations. Identification of fatigue biomarkers has important implications for understanding pathogenesis and defining novel therapeutic targets, but a paucity of evidence exists for fatigue biomarkers in SLE. The evidence for adipokines, reduced glutathione, iron deficiency, and vitamin D as potential biomarkers for SLE-related fatigue are reviewed. To address gaps in the SLE literature, the experience of each fatigue biomarker in other diseases is examined. Finally, biomarker associations with SLE pathogenesis and disease activity are discussed, as further rationale for investigation among SLE patients.
Keywords: biomarkers